REFLEKSI KEJUJURAN MASYARAKAT BUGIS DALAM PAPPASENGNA TO MACCAE RI LUWU SIBAWA KAJAO LALIQDONG RI BONE (Honesty Reflection of Buginese Society in ”Pappasengna To Maccae ri Luwu sibawa Kajao Laliqdong ri Bone”) - Mustafa Mustafa (Balai Bahasa Sulawesi Selatan, 2014)
Pappasengna To Maccae ri Luwu sibawa Kajao Laliqdong Bone is one of the classic oral literary of Buginese society conveyed by symbols. Will/advices implied still could be applied and preserved in Buginese society.It uses library research or literary study and dialectics discussions, as well as pragmatic and sociology ofliterary approachs. The data is collected and then analyzed. Data collection is done by library and fieldresearch. Will/advices are useful as a mean of education that could guide and find out the essence of humanexistence. The results of this study indicate that each person should be honest, good, and it is important thateach individual should always tell the truth, behave well, and keep promises, respect other’s rights, admitmistakes, avoid dissapointing others. Besides that, it also implies that each person must keep tongue, heart,and behavior of bad deeds.